Prototipo basado en transductor solar de bajo costo para el monitoreo de la irradiancia solar - Aldana Yarleque, Cristhian Nicolás (2024)
The main objective of the research is the design, construction and calibration of a low-cost prototype, based on a solar transducer, which allowed the monitoring of global solar irradiance in a certain geographic region of the city of Sullana. The prototype used two stages to collect data. 1) Detection stage, primary element of the measurement, a 65mm square polycrystalline photovoltaic cell was used; 2) Stage is the conversion of the analog signal to digital, a converter (ADC) was used. Information control is carried out by means of an ATM328P microcontroller; while the physical control of the devise is carried out using keypas. The data obtained is automatically saved to the internal memory og the device is carried ount using keypads. The data obtained is automatically saved to the internal memory of the device and simultaneously to a removable microSD card; The data is displayed on an OLED screen installed ford real-time monitoring. In addition, a Bluetooth module was incorporated for the transfer of respective data to a notebook, smartphone or PC.